PERANCANGAN SISTEM INFORMASI ABSENSI KEHADIRAN ONLINE BERBASIS WEB DI BALAI DESA NAGRAK - Seliwati Ginting; Risma Nur Afifah (POLITEKNIK PIKSI GANESHA, 2021)
This study aims to design and implement a web-based online attendance information system at the Nagrak Village Hall. The research method uses qualitative methods with a descriptive approach. Data collection techniques are used by observing, documenting and completing a literature review that is relevant to the problem. In the study, there was a problem of attendance using a manual system that was less effective and efficient. Therefore, it is necessary to design a web-based online attendance information system using UML (Unifiend Modeling Laguage) modeling language, implemented with a laravel framework ogramming language and data storage using MySQL. With this system as a web-based online attendance data processing can run effectively and efficiently.